Pengaruh Pengalaman Kerja, Karakteristik Individu Dan Iklim Organisasi Terhadap Kinerja Pegawai Badan Pengelolaan Pajak Dan Retribusi Daerah Provinsi Sumatera Utara - Sapta Harismada Tarigan; Robi Tanzil; Ananda Doly Putra Nasution; Rikki Zulhari; Elisabet Rita Karolina Simbolon; Sri Gustina Pane (Journal of Trends Economics and Accounting Research, 2022)
The Influence of Work Experience, Individual Characteristics and Organizational Climate on Employee Performance at Badan Pengelolaan Pajak Dan Retribusi Daerah Provinsi Sumatera Utara, guided by Mr. Dr. Nur. M. Ridha Tarigan, S.E.,M.M, as chairman, Mr. Dr. Syofyan, SE, M.Si and Mrs. Dr. Sri Gustina Pane, SE.,M.Si, as member, Thesis – 2022. The formulation of the problem in this study are: How do work experience, individual characteristics and organizational climate influence employee performance? This study aims to determine the effect of work experience, individual characteristics and organizational climate on employee performance. By using the Slovin formula and the Probalility Sampling technique, the sample is 88 people. The results are; Work experience partially has a positive effect on employee performance; Individual characteristics partially have a positive effect on the morale of employee performance; Organizational climate partially has a positive effect on employee performance; Work experience, individual characteristics and organizational climate simultaneously have a positive effect on employee performance